Demystifying International Publications: A Structured Training Model to Facilitate UIN SU Lecturers - Fithriani, Rahmah; Salmiah, Maryati (Universitas Negeri Malang, 2022)
Writing scholarly papers that meet international standards, such as those indexed by Scopus, has been a source of concern for lecturers at Universitas Islam Negeri Sumatra Utara (UIN SU) Me-dan, thus, became one of the factors that prompted this study. Employing R and D approach through ADDIE model, this research involved 20 lecturers from different educational backgrounds, skills, and units that represented the demographic site of UIN SU Medan as the participants. The results showed that the effective steps of training program for UIN SU Medan lecturers include the followings: 1) Conducting the training program for at least seven meetings; 2) Going through all the six steps of training; 3) Identifying the targeted journals; 4) Going through peer re-viewing process; 5) Improving writing ability: and the last, 6) changing perception. Those findings concluded that an effective training model that is also suitable for the lecturers’ needs is a training model that is like the findings of this study